Uma generalização do algoritmo de redução por pesos para p coordenadas - Solís Hidalgo, Jonathan Javier, 1991- (2024)
Orientadores: Carla Taviane Lucke da Silva Ghidini, Aurelio Ribeiro Leite de Oliveira